Determination of Methylene blue Number to Characterize the Lapsi Based Activated carbon Prepared by Chemical Carbonization - Shrestha, Rajeshwar Man (Journal of the Institute of Engineering, 2020)
Determination of Methylene blue Number of the activated carbons prepared by Chemical Carbonization from waste material, seed stone of Lapsi has been studied. Methylene blue Number has been determined by single point method using batch adsorption method. Acids like concentrated sulphuric acid and a mixture of concentrated sulphuric acid and concentrated nitric acid have been used to prepare activated carbon. The activated carbon prepared by using a mixture of concentrated sulphuric acid and concentrated nitric acid has been found to have higher methylene blue number than the activated carbon prepared by using concentrated sulphuric acid. The activated carbons thus prepared can be used as effective adsorbents for the remediation of pollutants from water.